Ecclesial and social relevance of the Dorotheas - D. Carlos Azevedo (Escola Superior de Educação de Paula Frassinetti, 2016)
By focusing the charism of the Congregation on the educational dimension in an evangelising education, we are led to place in this field the vision of the ecclesial and social relevance of the Dorotheas. Before pointing out some lines that characterize the actuality of a charism situated in the educational field, let us look at the pedagogical context of this beginning of the 21st century.